Optimization of nitrate reductase activity analysis and its characterization in sugarcane leaves - Santos, Carlos Leandro Rodrigues dos; Cazetta, Jairo Osvaldo; Saran, Luciana Maria; Sanches, Adhemar (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to standardize and characterize the conditions for determining the nitrate reductase activity in sugarcane leaf tissue, using in vivo method. Leaf samples were collected from a first ratoon crop of the IACSP 933046 cultivar, with six months of age. Different preparation conditions of leaf samples and incubation media were studied. The material that allowed the highest nitrate reductase activity was obtained by the sampling of 25 discs of 1 cm in diameter, collected at 13h from the center of the +1 leaf type without center rib. The incubation medium optimized to determine nitrate reductase activity in sugarcane leaves must be comprised of: 2.5 mL KNO3 300 mmol L‑1; 2.5 mL phosphate buffer 285 mmol L‑1 pH 7.3; 1.0 mL Tween 20 0.6% (v/v); and 4.0 mL deionized water. The highest nitrate reductase activity is obtained by incubating samples for 90 min, at 32°C, in the dark; is observed in young plants formed by stump sprouting; and reaches a minimum value at the plant maturity phase.